THE EFFECT OF SURFACTANTS IN REDUCING FUNGUS ON CABRETTA GOLF GLOVE LEATHER - Rahma Muktia Setyani; Emiliana Anggriyani; Laili Rahmawati (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
The purpose of this research is to identify the effect of surfactants on the loss of mold found in the crust skin of the cabretta golf glove article. The raw materials used are 2 sheets of moldy cabretta golf glove article crust, with an average thickness for trial 1 0,54 mm, and trial 2 0,52 mm. The chemicals used are water, Peramit MLN, Preventol CR, and Formic Acid. The method used in trials 1 and 2 carried out skin washing with a surfactant concentration of 0,1% and 0,2%, activities carried out with washing within 30 minutes. Organoleptic test results in both trials, the fungus was lost but with little trace. In addition, in trial 1's skin has a fairly flat color, a non- leakable state of nerves, and a tightness to the standards. Trial 2 skin has a flat color, a non- leaking nerf, and a tightness to the standards. The physical test results show skin softness values are 6,4 mm (trial 1) and 6,6 mm (trial 2). The conclusion is that using 0,1% surfactant, it can reduce the defect present in the skin of the article cabretta golf glove but with little trace and the softness remains up to standards.